Istihsan dan Pembaruan Hukum Islam - Darmawati H (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2011)
Ishtisan is one source ijtihad, which means assuming something better to achieve a kemaslahatan. Ishtihsan be used as evidence because they are more able to realize the objectives of shari'ah. Scholars who use ishtihsan as a source of Islamic law of which the Imam Abu Hanifah, Imam Malik and some followers of Imam Ahmad bin Hanibal.Kaitan ishtihsan with legal reform lies in the maqasid Islamic Shari'a, which aims to realize and maintain the benefit of mankind.